National policy styles in theory and practice - Howlett, Michael; Tosun, Jale (The Routledge handbook of policy styles, 2021)
Studies examining styles have tended to focus on the national level and to contend that policy-making processes need to be studies through the lens of the manner in which the institutional make-up of a government generates the routines and standard operating procedures which constitute its decision-making structure and processes. Given the interest of comparative policy analysis in the patterns and sources of policy change, the concept of a national policy style helps further our understanding of the relationship between politics and policy. By the mid-1970s it was apparent to many academic observers that actors in the policy-making process tend to take on, over a period of time, a distinctive style which affects policy decisions. That is, they develop tradition and history which constrains and refines their actions and concerns. The concept of a national policy style not only helps to describe typical policy processes and deliberations that may or may not lead to policy change, but also helps capture an important aspect of policy dynamics, that is, the relatively enduring nature of these arrangements.